Multimodal Discourse Analysis on Motivational Hustle Culture Quotes - Christina Christina; Risky Shasita (Faculty of Language and Literature, Universitas Sains Al-Qur'an, 2022)
This study is aimed to analyze how the verbal and visual aspects in motivational hustle culture quotes make meaning in the quote. The researcher uses a qualitative approach so that the result will be in descriptive analysis. In doing the analysis the researcher uses Systemic Functional Linguistics to analyze the verbal aspect and Visual Semiotic of the Barthian and Salience theory and both lean on the Multimodal Discourse Analysis (MDA) as the grand theory. The result shows that from the verbal aspect, among the 30 images that are being used, 21 of them use declarative as the communicative purpose, 9 imperative clauses, 5 relational processes, 1 material process and all of the 30 clauses have Textual Metafunction. Subsequently from the semiotic aspect, there are 17 images that only contain literal meaning and 13 metaphorical meaning. Then 18 of them use cool tones and 19 of the images in conjunction with the photography technique use medium shots.